Arnalte, Cardenio, and "The Second Maiden's Tragedy": from narrative to theater - Albuixech, Lourdes (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
The genre known today as sentimental narrative was widely popular at its time and even later. Some of the fictions enjoyed an abundant readership, were translated into other languages, and came lo influence such masterpieces as Cervantes' Don Quixote. The "Tale of Cardenio and Luscinda"  in Don Quixote is strikingly similar to the Tractado de amores de Arnalte y Lucenda, one of Diego de San Pedro's contributions to the genre. Aside from plot coincidences, both fiction and tale make use of theatrical devices. Not suprisingly, Cervantes' tale was lhe model to a british play known to scholars as The Second Maiden's Tragedy, which has been atributed to Shakespeare and Fietcher. In this article I study the relationship between the three texts and lhe twists and turns of a fabula that, first created as narrative, came to be drama two centuries later.
Keywords: Miguel de Cervantes; Diego de San Pedro; The Second Maiden's Tragedy